Success Factors in Logistics Outsourcing - Grahl, Alexander; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Business relationships between customer firms and their logistics service providers represent an increasingly important element of today$1 (Bs supply chains and thus, the success of such logistics outsourcing relationships has crucial relevance for the competitiveness of a supply chain. With his three papers on success factors in logistics outsourcing, Alexander de Grahl provides relevant insights regarding this important research question. In detail, adopting different perspectives in the three papers, the work shows how logistics service providers, customer firms and the two parties together can contribute to successful logistics outsourcing relationships.s
Keywords: Economics; Economics/Management Science; Production/Logistics/Supply Chain Management